Car B because 334 divided by 5= 41 mph
X = - 1/3 or an alternate form x = -0.3, x = -3 to the power of -1
Answer:
<u>Square</u>
Step-by-step explanation:
Requirements that make a square, a square;
- Four sides
- Congruent angles (all 90°)
- Opposite sides are congruent/the same.
- Opposite sides are also parallel because the lines of a square do not intersect.
Answer:
1 / (x-2)(x+3)
Step-by-step explanation:
Given in the question the expression:
(x + 1) / (x² + x - 6) ÷ (x² + 5x + 4) / (x+4)
factorisation of (x² + x - 6) = (x-2)(x+3) by using quadratic equation
(x + 1) / (x-2)(x+3) ÷ (x² + 5x + 4) / (x+4)
Taking reciprocal to convert ÷ into ×
(x + 1) / (x-2)(x+3) x (x+4) / (x² + 5x + 4)
factorisation of (x² + 5x + 4) = (x+1)(x+4) by using quadratic equation
(x + 1) / (x-2)(x+3) x (x+4) / (x+1)(x+4)
cancel (x + 1) from both expression
1 / (x-2)(x+3) x (x+4) / (x+4)
cancel (x+4)
1 / (x-2)(x+3) Simplified form
Given the equation: (km / 3) - 2x = 4, it is essential to isolate x to obtain the expression to solve it. This is done below:
(km / 3<span>) - 2x = 4
</span>
Adding 2x to both sides:
(km / 3<span>) - 2x + 2x = 4 + 2x
</span>(km / 3<span>) = 4 + 2x
</span>
Subtracting 4 from both sides:
(km / 3<span>) - 4 = 4 + 2x - 4
</span>(km / 3<span>) - 4 = 2x
</span>
Dividing 2 from both sides:
[(km / 3<span>) - 4] /2 = 2x /2
</span>[(km / 3<span>) - 4] /2 = x
</span>x = (km / 6) - 2